Where Does Inequality Come From? Ideas and Implications for Latin America - Robinson, James A.. (OECD Development Centre Working Papers, 2001)
Differences in inequality between Latin American countries are not so much caused by globalisation as by a variety of political and economic structures and government policies. Hostile elites have made democracy fragile and are delaying the mass education and tax-driven income redistribution that democratisation and socialism produced in Europe over the past century. Trends in inequality in Latin America are governed by coups and democratic phases. Recent rising inequality in Argentina, Chile and Peru is mostly due to structural changes in the balance of political power triggered by policies of the military and the debt crisis. The demobilisation of labour and the left has led to new political coalitions that have seriously reduced the chances of democracy playing the key role it did in changing Europe. In theory, globalisation can increase inequality through its impact on prices or wages or by curbing the government's ability to implement policies. In fact there is little evidence ...